Huyang Yangkun formula regulates the mitochondria pathway of ovarian granulosa cell apoptosis through FTO/m6A-P53 pathway - Yang Li; Lingdi Wang; Jian Liu; Guangning Nie; Hongyan Yang; Hongyan Yang (Frontiers Media S.A., 2024)
BackgroundPremature ovarian insufficiency (POI) presents a significant challenge to female reproductive health. The Huyang Yangkun Formula (HYF), a traditional Chinese medicinal formulation, has been utilized in clinical settings for the treatment of POI for over a decade. Nevertheless, the therapeutic application of HYF is considerably constrained by the lack of clarity regarding its underlying mechanism of action.MethodsThe experimental procedures entailed administering VCD to female Sprague-Dawley rats at a dosage of 160 mg/kg/day over a period of 15 days, succeeded by a 100-day treatment with HYF. Blood serum samples were collected and analyzed using ELISA to quantify the concentrations of Anti-Müllerian Hormone (AMH), Follicle-Stimulating Hormone (FSH), and Estradiol (E2). The levels of N6-methyladenosine (m6A) were assessed through Dot blot analysis and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Western blotting was employed to validate the differential expression of m6A-related catalytic enzymes and apoptosis-related regulators, including BCL-2, BCL-XL, and MCL-1, which may be implicated in the effects of HYF. Certain shRNA-COV434 cell line was constructed for the exploration of molecular mechanism, and then the potential targets were finally verified by MeRIP-qPCR.ResultsHYF has been identified as having a significant influence on the development of residual ovarian follicles in rats with POI, especially during the initial stages. It was observed that HYF facilitates the progression of escaping antral follicles to full maturation. Additionally, HYF exhibited the capacity to enhance the proliferation of COV434, a human ovarian granulosa cell line, while concurrently inhibiting apoptosis within these cells. Notably, HYF treatment resulted in the downregulation of apoptotic proteins, including BCL-XL, cleaved-caspase 9, cleaved-caspase 3, and Bcl-2. Concurrently, m6A modification is implicated in the regulation of HYF. Both in vitro and in vivo studies indicate that FTO may play a role in the anti-apoptotic mechanisms mediated by m6A in ovarian granulosa cells influenced by HYF. Moreover, employing qPCR and MeRIP-qPCR techniques, P53 has been identified as the target gene for m6A modification mediated by FTO.ConclusionThese findings suggest that HYF holds promise as a potential treatment for POI and provide a more comprehensive understanding of the mechanism by which HYF operates, specifically its ability to prevent the BCL-2 mitochondrial apoptosis pathway mediated by P53 in ovarian granulosa cells of POI rats by regulating FTO/m6A-Tp53.